Respuesta :
a₁ = 5 an = a₁ + ( n-1) * r
wyliczymy jednak - so we enumerate
a₁ = 5 + (1-1) * (1/6) = 5 + 0* 1/6 = 5 + 0 = 5
a₄ = 5 + (4 - 1) * (1/6) = 5 + 3 * (1/6) = 5 + 3/6 =5 1/2 = 5,5
a₁₀ = 5 + (10 - 1) * (1/6) = 5 + 9 * (1/6) = 5 + (9/6) = 5 + 3/2 = 6 1/2 = 6,5
wyliczymy jednak - so we enumerate
a₁ = 5 + (1-1) * (1/6) = 5 + 0* 1/6 = 5 + 0 = 5
a₄ = 5 + (4 - 1) * (1/6) = 5 + 3 * (1/6) = 5 + 3/6 =5 1/2 = 5,5
a₁₀ = 5 + (10 - 1) * (1/6) = 5 + 9 * (1/6) = 5 + (9/6) = 5 + 3/2 = 6 1/2 = 6,5
Answer:
First term is 5
Fourth term is 5.5
Tenth term is 6.5
Step-by-step explanation:
Given :The rule as [tex]A(n)=5+(n-1)(\frac{1}{6})[/tex]
We have to find find the first,fourth,and tenth terms of the arithmetic sequence.
Consider the given rule ,
[tex]A(n)=5+(n-1)(\frac{1}{6})[/tex]
For first term , put n = 1
[tex]A(1)=5+(1-1)(\frac{1}{6})[/tex]
Simplify , we have,
[tex]A(1)=5[/tex]
For fourth term, Put n = 4
we have,
[tex]A(4)=5+(4-1)(\frac{1}{6})[/tex]
Simplify, we have,
[tex]A(4)=5+(3)(\frac{1}{6})[/tex]
[tex]A(4)=5+\frac{1}{2}=5.5[/tex]
For tenth term, put n = 10 ,
We have,
[tex]A(10)=5+(10-1)(\frac{1}{6})[/tex]
[tex]A(10)=5+(9)(\frac{1}{6})[/tex]
[tex]A(4)=5+\frac{3}{2}=6.5[/tex]
Thus, First term is 5
Fourth term is 5.5
Tenth term is 6.5